an investigation into conceptual metaphors of “moon” and “trăng” in english and vietnamese poetry in the 19th and 20th centuries - Nguyễn,Võ Thị Thu Hiền. (2016)
This thesis carried out an investigation into conceptual metaphors of “moon’’ in English and “trăng” in Vietnamese in the 19th and 20th century poetry. This is an attempt to find out the similarities and differences of conceptual metaphors of “moon” and “trăng” used in 19th and 20th century poems in English and Vietnamese. To achieve the purposes, this paper chose the descriptive, comparative, quantitative and qualitative approaches throughout the study. There are 449 metaphorical expressions of “moon” and “trăng” collected from English and Vietnamese poems in books, journals and on the Internet. The result shows that there are ten interesting source domains occur in conceptual metaphors of “moon” (“trăng”) in English, Vietnamese, or both. They are: A PERSON, A CONTAINER, AN OBJECT, A PLANT, AN ANIMAL, FOOD AND DRINK, A DESTINATION, WATER, and A COVER. Besides, there were also findings about similarities and differences of conceptual metaphors of “moon” used in poetry between the two languages. The differences were found through the differences in language using, through the different frequency of occurrence and through some source domains which are used in one language but were not in another one. The research also suggests some implications for teaching, learning and translating of conceptual metaphors, which are useful for Vietnamese learners of English to be successful in cross-cultural communication.